2012
DOI: 10.1093/hmg/dds180
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of social interaction through genetic and environmental manipulation of the 22q11.2 gene Sept5 in the mouse brain

Abstract: Social behavior dysfunction is a symptomatic element of schizophrenia and autism spectrum disorder (ASD). Although altered activities in numerous brain regions are associated with defective social cognition and perception, the causative relationship between these altered activities and social cognition and perception-and their genetic underpinnings-are not known in humans. To address these issues, we took advantage of the link between hemizygous deletion of human chromosome 22q11.2 and high rates of social beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 79 publications
(69 reference statements)
0
60
0
1
Order By: Relevance
“…Giovanoli and colleagues showed how unpredictable stress during puberty resulted in PPI deficits and increased sensitivity to amphetamine and MK-801 in mice exposed to prenatal immune activation. In addition, Harper and colleagues 22 showed how reduced social interaction in Sept5 knockout mice, one of the 22q11.2 genes, could be rescued by reducing the level of stress, clearly demonstrating a genotype × environment interaction.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Giovanoli and colleagues showed how unpredictable stress during puberty resulted in PPI deficits and increased sensitivity to amphetamine and MK-801 in mice exposed to prenatal immune activation. In addition, Harper and colleagues 22 showed how reduced social interaction in Sept5 knockout mice, one of the 22q11.2 genes, could be rescued by reducing the level of stress, clearly demonstrating a genotype × environment interaction.…”
Section: Limitationsmentioning
confidence: 99%
“…Genetic background 21 and environmental factors 22 may influence phenotypic expression. To be able to control for these factors and ensure sufficient access to mice we have generated a new congenic mouse model Clozapine or haloperidol challenges…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to define the molecular and cellular basis of the cognitive and behavioral deficits associated with the 22q11.2 microdeletion have focused on the effects of single gene mutations within the 22q11.2 microdeletion region (Bender et al, 2005; Chun et al, 2014; Fenelon et al, 2013; Harper et al, 2012; Hiramoto et al, 2011; Hsu et al, 2007; Huotari et al, 2004; Mukai et al, 2004; Murphy et al, 1999; Paterlini et al, 2005; Xu et al, 2013). Recently, we demonstrated that mice haploinsufficient for one of these genes, Zdhhc8 +/− , recapitulate several key aspects of the full microdeletion, including deficits in spatial working memory and functional connectivity (Mukai et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The gene is located within 22q11 region linked to schizophrenia (Harper et al, 2012). SEPT5 is expressed in the brain both during neurodevelopment and adulthood (Asada et al, 2010) and is involved in vesicular exocytosis by binding to syntaxin in presynaptic SNARE (Soluble N-ethylmaleimide-sensitive factor Attachment Protein Receptor) complexes (Beites et al, 2005).…”
Section: Gene-environment Interplaymentioning
confidence: 99%
“…Compared to group-housed mutants, single-housed ones demonstrated less thigmotaxis in open field, spent more time in the open arms of the elevated plus maze and spent more time in active social interaction compared to group housed mutants, consistent with reduced anxiety levels. This study is another example where adverse factors interact to counteract the negative effects of one another when studied separately (Harper et al, 2012). …”
Section: Gene-environment Interplaymentioning
confidence: 99%